Evaluation and Analysis of Variance of Storage Stability of Asphalt Binder Modified by Nanotitanium Dioxide. (10th October 2017) - Zou, Xiaolong; Sha, Aimin; Ding, Biao; Tan, Yuqiao; Huang, Xiaonan
Abstract : To investigate the effects of nanoparticle content, storage time, and storage temperature on the storage stability of asphalt binders modified by nanoparticles, hot tube storage tests, softening point tests, and dynamic-shearing rheometer (DSR) tests were adopted to evaluate the properties of two kinds of nanotitanium dioxide (TiO2 ) modified asphalt binders. A statistical one-way analysis of variance (ANOVA) test was employed to analyze the effects of those variations on the storage stability of the nano-TiO2 modified asphalt binders. The results indicated that the softening point, the failure temperature, the dynamic-shear viscosity, and G ⁎ / s i n δ of the binders increased with nanoparticle content. The storage stability of the binders decreased with nanoparticle content. The impact of storage time on the storage stability of the binders was remarkable when the storage time was more than 48 h. Moreover, the storage stability of the binders at low temperatures was better than that at high temperatures. Based on the one-way ANOVA, the size of nanoparticle had little influence on the storage stability of the nano-TiO2 modified asphalt binders in this study. Reducing the nanoparticle size cannot effectively enhance the storage stability of the nanoparticle modified asphalt binder due to the agglomeration of nanoparticle.